Chapter 1 Immigrants being at home in libraries How the immigrants brought their home to the New York Public Library - Dalbello, Marija (Taylor & Francis, 2022)
The first two decades of the twentieth century were formative for the library services for immigrants being established in the New York Public Library. The library's literacy and citizenship activities were the grounds for the social transformation by which immigrants would become denizens of New York. This essay interprets the material practices and discursive representations of that period in the library's institutional records that conveyed sanctioned versions of material culture of books and reading aimed at immigrants and contrasting them to other narratives and moral explanations that exposed the frictions and thresholds by which bodies, books, affects, and senses shaped the library as a place for immigrants and their "lived" use of the library. The language evocative of dirt and pollution brought to books and reading in the immigrant neighborhoods transferred the materiality of the immigrants' tenement dwellings to the library spaces and reveals a contiguity between the library home and the tenement home.